Fast food restaurant industry scenario in Malaysia:college students' perceptions / Ahmad Esa Abdul Rahman , Sharifah Nadzrah Syed Omar - Abdul Rahman, Ahmad Esa; Syed Omar, Sharifah Nadzrah (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2009)
The proliferation of fast food restaurants is one of the most notable developments in the Malaysian foodservice industry. The sector has grown at a rapid rate over the past 20 years. Despite the continuing debate in western countries about fast food's role and contributions toward the deterioration of public health, the industry is believed to be benefiting from current local demographic trends, urbanization and changing lifestyles. Given that college students are considered as major customers of the fast food industry, it is noteworthy to investigate how they perceive the industry in Malaysia. The study initially explores college students' perceptions of fast food restaurant's service quality. It also examines the attributes that influence consumer preferences for fast food restaurants and analyses different fast food brand positions in the college market. This quantitative study was conducted at various public and private higher learning institutions in Klang Valley. A survey was conducted through distributing questionnaires to college students from different academic programs. A total of 1000 self-administered questionnaires were distributed with a 98.5% response rate. Using quantitative analysis, the data was computed and analyzed by using SPSS program. The results indicate that college students perceive fast food restaurants in Malaysia to be of a high quality. Their fast food restaurant choices were strongly influenced by the restaurant's cleanliness, consistency of menu items, and location. The results further suggest that McDonald's is the strongest fast food brand in Malaysia, followed by KFC and then Burger King, giving a clear dichotomy between those restaurants that have an established image and those that have not. Marketers need to identify the factors that local customers consider more important when making a decision on the selection of a fast food restaurant, and their marketing strategies should have a sound understanding of consumer perceptions and preferences and how they differ across different cultures.